Advances in molecular diagnosis of tuberculosis - MacLean, Emily; Kohli, Mikashmi; Weber, Stefan F.; Suresh, Anita; Schumacher, Samuel G.; Denkinger, Claudia M.; Pai, Madhukar (Journal of clinical microbiology, 2020)
Molecular tests for tuberculosis (TB) have the potential to help reach the three million people with TB who are undiagnosed or not reported each year and to improve the quality of care TB patients receive by providing accurate, quick results, including rapid drug-susceptibility testing. The World Health Organization (WHO) has recommended the use of molecular nucleic acid amplification tests (NAATs) tests for TB detection instead of smear microscopy, as they are able to detect TB more accurately, particularly in patients with paucibacillary disease and in people living with HIV. Importantly, some of these WHO-endorsed tests can detect mycobacterial gene mutations associated with anti-TB drug resistance, allowing clinicians to tailor effective TB treatment. Currently, a wide array of molecular tests for TB detection is being developed and evaluated, and while some tests are intended for reference laboratory use, others are being aimed at the point-of-care and peripheral health care settings. Notably, there is an emergence of molecular tests designed, manufactured, and rolled out in countries with high TB burden, of which some are explicitly aimed for near-patient placement. These developments should increase access to molecular TB testing for larger patient populations. With respect to drug susceptibility testing, NAATs and next-generation sequencing can provide results substantially faster than traditional phenotypic culture. Here, we review recent advances and developments in molecular tests for detecting TB as well as anti-TB drug resistance.
Gesehen am 27.11.2020